The Role of Alcohol in Deaths due to Stab Wound Injuries - Türkmen, Nursel; Fedakar, Recep; Çetin, Volkan; Durak, Dilek (The Bulletin of Legal Medicine, 2002)
Background: The aim of this study is to evaluate the role of alcohol and psycho-active substances in deaths due to stab wounds. Material and Method: 240 (6,71%) deaths due to stabbing, of total 3575 forensic autopsy cases performed in Council of Forensic Medicine Bursa Morgue Department between the years 1996-2002, are evaluated retrospectively. Cases are examined according to their age, sex, origin, blood alcohol concentration, drugs in blood, urine, organ samples and gastric contents. Results: 204 (85%) cases of total 240 are male and 36 (15%) are female. In 73 (%) of the cases alcohol has been detected and blood alcohol concentration varies between 44% and 280%. 71 (97,26%) of alcohol detected 73 cases are male and 28 (38,35%) of 73 are in the age group of 30-39. In one case, carbamazepine is detected in urine, stomach content and organ samples. Conclusion: In Bursa and surroundings, alcohol, even though has a low ratio comparing to cities and countries which we searched through literature, has a significant role in deaths due to stab wounds, but the role of the other drugs is extremely low. Key words: Stab wounds, death, autopsy, alcohol, drug